Identification of Performance in The Base Population of Male Indigenous Chickens in Leihitu Barat District Central Maluku Regency - Sarfan, Riri; Rajab, Rajab; Papilya, Bercomien Juliet; Matatula, Michel Johan (Bulletin of Applied Animal Research, 2025)
This study was conducted to identify the performance characteristics of local (Kampung) chickens within a production system and to evaluate their productive potential as prospective sires for meat production in village-level breeding programs in Leihitu Barat District, Central Maluku Regency. Observations and measurements were carried out on 206 chickens aged over 22 weeks, owned by 15 local farmers in five purposively selected villages. The selection of respondents and chicken samples was conducted using a stratified sampling method, with the expectation that these chickens could be utilized in a village-scale breeding scheme. The performance parameters observed included body weight, chest circumference, wing length, thigh length, shank length, and the length of the third toe (J3). The selection of the base population of local chickens as potential sires for meat production was grouped using a normal distribution based on body weight clusters. The results of the study showed that, based on body weight performance and morphometric character analysis (body weight, chest circumference, wing length, thigh, shank, and third toe length), male native chickens in the five villages exhibited significant genetic variation, particularly in body weight, with coefficients of variation (CV) exceeding 30% in most villages. The highest variation in body weight was observed in Liliboy Village (CV 1,27%) and Hattu Village (CV 0,38 %), indicating chicken populations with highly diverse genetic backgrounds. More stable and directed variation was found in Allang and Hattu Villages, where most traits showed moderate CVs (10–30%). Keywords: Local Chicken, Identification, Performance, Base Population Selection.